Penggunaan Roujingo dalam Anime Bahasa Jepang - Julius Christian, Mikhael; Dirgandini, Melinda (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
This study aims to describe the different nuances produced in characters who use roujingo ???   in anime and describe the differences between the use of roujingo ???   in anime and reality. Japanese has a standardized language variety called hyoujungo ??? . Within hyoujungo ??? , there is another language variety called yakuwarigo ???   which means role language. Kinsui (2017) divides yakuwarigo ??? into 6 types. The researcher is interested in examining one type of ??? yakuwarigo based on the age of the language user, namely rounen ?? or roujingo ??? or the language of seniors. roujingo ??? is the language used by characters who are depicted with moustaches white hair and old faces. This research method is descriptive qualitative, which is research conducted to determine the value of independent variables, either one or more variables (independent) without making comparisons or connecting with other variables. The descriptive qualitative research method is used in this study to describe the existing facts of the use of roujingo in anime. The research data was taken from 8 anime published in the period 2000-2022. The data was analyzed by looking at the use of roujingo ???   from anime characters with different social statuses. The conclusion of this study is that the author found two different functions of using roujingo ???  . First, as a marker of parental nuance. Second, as a marker of grandeur and power, indicating high social status and power. Another finding of this study is that roujingo ???   is not used by old people suddenly. Japanese people do not change their language to that of their parents when they reach old age. Instead, the use of roujingo ???   is limited to works such as anime and manga, used to portray old, regal, and powerful roles.